(untitled) (Research, Society and Development, 2021)
Oral cancer is a neoplasm that affects the labial region and the oral cavity, considered the most common type of neoplasia in Brazil and in the world, occupying the sixth position in cancer mortality rates. According to the National Cancer Institute (INCA), 2020, it has an estimate of about 15,190 new cases of oral cancer in Brazil. The aim of this study was to carry out an integrative review of the current literature on the early diagnosis of oral cancer with precision using artificial intelligence tools, highlighting its technique, indications, limitations and disadvantages. An integrative literature review was carried out through a search for scientific articles in the electronic database PubMed, Scielo and Medline using the descriptors: oral neoplasms, diagnosis and artificial intelligence, indexed in the period from 2016 to 2020 that dealt with case reports , in vitro and ex vivo study. After the eligibility criteria, 11 articles fully published in English were allowed. The advanced studies that the technique brings more to the early diagnosis of oral cancer in asymptomatic patients who are safe or under suspicion, decreasing according to the chances of evolution of the neoplasia, contributing to the best treatment approaches.